Reflection on the Value of Cultural Construction under the Background of Generative Artificial Intelligence - Tan, Manman (Journal of Theory and Practice of Management Science, 2025)
Generative artificial intelligence (AIGC) is a globally recognized strategic frontier technology that has been widely applied in various creative fields. Generative artificial intelligence not only brings convenience to human society, but also inevitably challenges the existing value of humanity. In the context of accelerating the spillover of information dissemination technology and the strategy of building a strong cultural country, strictly controlling the value challenge of generative artificial intelligence to cultural construction is a major issue that must be solved in the new era. On the basis of summarizing the meaning and basic fields of generative artificial intelligence technology, this article analyzes the value challenges and difficulties faced by contemporary cultural construction from the perspective of generative artificial intelligence: ethical impact caused by the ambiguity of AIGC related norms, human value alienation caused by technological dependence on AIGC, and value interference caused by the manipulability of AIGC data corpus. Summarize its development experience and seek a value reconstruction path for generative artificial intelligence and cultural construction.